KEMISKINAN PERKOTAAN: STRATEGI PEMULUNG DI KOTA AMBON - Amelia Tahitu; Cornelly M.A. Lawalata (Politeknik Kesejahteraan Sosial, 2017)
AbstractScavengers are part of the urban poor communities that their daily activities in the informal sector by collecting used goods sold for revenue. Scavengers do not require the formal requirements and easy job to do, but full of challenges and risks. Work life scavenger is a challenge that must be done because of poverty conditions and anticipate the household income. In the administration of the city of Ambon has 5 districts namely Ambon Bay Baguala districts, Sirimau, Nusaniwe, Ambon Bay, and South Leitimur. UPTD IPST data from the Office of Ambon in 2016, the number totaled 230 Scavenger scattered in districts Sirimau, Nusaniwe, and South Leitimur. This research was conducted in four districts namely: Sirimau, Nusaniwe, Baguala, and South Leitimur, as scavengers scattered in the districts. Tthe aim of this study was to describe the causes of poverty in poor communities scavengers, identify factors ignorance about household financial management of poor scavengers community, and formulate urban poverty reduction strategies are effective. The method used is quantitative descriptive, WITh data collection techniques; observation, interviews, and questionnaires. Data were analyzed using descriptive methods. The results achieved by the characteristics of the pemulungt sample (scavengers), WITh low income, standard of uninhabitable housing, low health status, education and knowledge is inadequate and results in the inability to manage household finances well. This resulted in them (scavengers) barely have a plan for the future of the family, including the children's education.Keywords: Scavengers, poverty, Ambon. AbstrakPemulung merupakan bagian dari komunitas miskin perkotaan yang aktivitas kesehariannya pada sektor informal dengan melakukan pengumpulan barang bekas untuk dijual demi memperoleh pendapatan. Pemulung tidak memerlukan persyaratan formal dan pekerjaannya mudah untuk dilakukan, namun penuh tantangan dan resiko. Pekerjaan pemulung merupakan tantangan hidup yang mesti dilakukan karena kondisi kemiskinan dan mengantisipasi pendapatan rumahtangga. Secara administrasi Kota Ambon memiliki 5 kecamatan yakni Kecamatan Teluk Ambon Baguala, Sirimau, Nusaniwe, Teluk Ambon, dan Leitimur Selatan. Dari data Kantor UPTD IPST Ambon tahun 2016, jumlah Pemulung yang memiliki kartu yang tersebar berjumlah 230 pada kecamatan Sirimau, Nusaniwe, dan Leitimur Selatan. Penelitian ini dilakukan pada 4 kecamatan yakni: Sirimau, Nusaniwe, Baguala, dan Leitimur Selatan, karena pemulung tersebar pada kecamatan tersebut. Tujuan dari penelitian ini adalah untuk menggambarkan faktor penyebab kemiskinan menurut komunitas miskin pemulung, mengetahui faktor ketidaktahuan tentang manajemen keuangan rumah tangga komunitas miskin pemulung, dan merumuskan strategi pengentasan kemiskinan perkotaan yang efektif. Metode yang digunakan adalah deskriptif kuantitatif, dengan teknik pengumpulan data; observasi, wawancara, dan angket. Data dianalisis dengan menggunakan metode deskriptif. Hasil yang dicapai berdasarkan karakteristik pemulung (pemulung), dengan tingkat pendapatan yang rendah, standart rumah tidak layak huni, derajat kesehatan rendah, pendidikan dan pengetahuan yang minim sehingga mengakibatkan ketidakmampuan dalam mengelola keuangan rumah tangga dengan baik. Hal ini mengakibatkan mereka (pemulung) nyaris tidak memiliki perencanaan untuk masa depan keluarga termasuk pendidikan anak-anak.Kata Kunci: Pemulung, kemiskinan, Ambon.